2013
DOI: 10.1186/1129-2377-14-12
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality, arousal and pain thresholds in migraineurs: a blinded controlled polysomnographic study

Abstract: Background: Our aim was to compare subjective and objective sleep quality and arousal in migraine and to evaluate the relationship between sleep quality and pain thresholds (PT) in controls, interictal, preictal and postictal migraine. Methods: Polysomnography and PT (to pressure, heat and cold) measurements were done in 34 healthy controls and 50 migraineurs. Subjective sleep quality was assessed by sleep diaries, Epworth sleepiness scale, Karolinska sleep questionnaire and Pittsburgh sleep quality index. Mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 43 publications
5
63
0
Order By: Relevance
“…In a recent PSG study of migraine sufferers, shorter sleep latency was observed in the preictal phase relative to the interictal phase. 35 Methodological differences notwithstanding, these two findings appear to suggest that an acute pain increase in a chronic pain condition may be related to shorter sleep latency. 35 While no details on medication use among migraine sufferers were reported, 35 in the present sample of women with TMD the relationship between pre-sleep pain ratings and sleep latency was apparently mediated by the use of opioid medications.…”
Section: Pain and Covariate Predictorsmentioning
confidence: 88%
“…In a recent PSG study of migraine sufferers, shorter sleep latency was observed in the preictal phase relative to the interictal phase. 35 Methodological differences notwithstanding, these two findings appear to suggest that an acute pain increase in a chronic pain condition may be related to shorter sleep latency. 35 While no details on medication use among migraine sufferers were reported, 35 in the present sample of women with TMD the relationship between pre-sleep pain ratings and sleep latency was apparently mediated by the use of opioid medications.…”
Section: Pain and Covariate Predictorsmentioning
confidence: 88%
“…Recording details are presented elsewhere (9)(10)(11). All participants filled in sleep diaries 2 weeks before and 2 weeks after measurement of pain thresholds and subsequent polysomnography.…”
Section: Methodsmentioning
confidence: 99%
“…The method is described in detail elsewhere (9)(10)(11). One hundred and twenty-six persons, 85 women and 41 men, (age range 18-64, mean age 38.9 years), including 41 healthy controls, 24 TTH, and 61 migraine patients participated in this study (Fig.…”
Section: Participantsmentioning
confidence: 99%
“…Interictal migraineurs may have lower thermal pain thresholds compared to controls (Schwedt et al , 2011, Engstrom et al , 2013. The pain thresholds may further decrease right before and during migraine attack (Burstein et al , 2000, Sand et al , 2008.…”
Section: Introductionmentioning
confidence: 99%